Seafloor Structures and Static Stress Changes Associated With Two Recent Earthquakes in Offshore Southern Batangas, Philippines - Sarmiento, Keanu Jershon S.; Aurelio, Mario A.; Flores, Paul Caesar M.; Carrillo, Anne Drew V.; Marfito, Bryan J.; Abigania, Maria Isabel T.; Daag, Arturo S.; Siringan, Fernando P. (Frontiers in Earth Science, 2022)
The 1994 Mw 7.1 Mindoro Earthquake and the 2017 Mw 5.9 Batangas Earthquake Sequence both occurred in offshore southern Batangas and devastated southern Luzon and Mindoro. These earthquakes exhibited NW-striking right-lateral slip in an area presumably defined by a WNW-striking left-lateral fault, therefore implying the existence of previously unmapped offshore faults. High resolution multibeam bathymetry grid and subbottom profiles revealed a conjugate strike-slip fault system under an approximately EW-directed extension. NW-striking right-lateral faults (F1 Faults: Central Mindoro Fault, Aglubang River Fault and Batangas Bay Fault System) bound the western part of the study area. On the other hand, a series of almost parallel NE-trending left-lateral and normal faults (F2 Faults: Macolod Corridor, North Verde Fault System, Central Verde Fault System, South Verde Fault and Northeast Mindoro Fault System) approach the F1 faults from the northeast. The distribution of the 1994 and 2017 earthquakes suggests that the possible rupture areas for these events are the Aglubang River Fault and the southwest Batangas Bay Fault System, respectively. These two traces appear to be connected and a restraining bend is suggested to have acted as a rupture barrier between the two events. Coulomb stress transfer modeling showed that the 1994 earthquake promoted the failure of the 2017 earthquake. Furthermore, results from the stress transfer models showed stress increase on the F1 faults (Batangas Bay Fault System and Central Mindoro Fault) and the northern F2 faults (North Verde Fault System and Central Verde Fault System). The newly recognized faults redefine the knowledge of the neotectonic structure of the area but are still consistent with the ongoing east-west extension in southern Luzon and the overall extension in northern Central Philippines. These faults pose seismic hazards, and more studies are needed to determine their seismogenic potential.